Strategi Efektif untuk Mencegah Bullying di Madrasah Ibtidaiyah - Fadiyah, Lisa; Suharsono (IBTIDA’, 2025)
Bullying is a common issue among children and can negatively impact their mental health and academic performance, including in Islamic elementary schools (madrasah ibtida’iyah). This study aimed to identify effective strategies for preventing bullying in madrasah by incorporating Islamic values. A systematic literature review was conducted on relevant studies published between 2020 and 2025, using a qualitative descriptive approach. The collected data were analyzed using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The findings indicate that instilling Islamic values such as honesty, tolerance, compassion, and social awareness plays a crucial role in shaping students’ character, fostering mutual respect, and developing empathy. Religious activities in schools, such as reading the Qur’an, performing congregational prayers, and learning Islamic ethics, serve as essential means to reinforce these values in daily life. Additionally, teachers’ roles as role models and collaboration with parents are key factors in creating a safe and harmonious school environment. Therefore, strategies based on Islamic values have the potential to reduce bullying in madrasah ibtida’iyah and promote a positive and supportive learning environment for students’ character development.